Pemikiran Islam Modern Syed Muhammad Naquib Al-Attas - Makhfira Nuryanti; Lukman Hakim (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2020)
Al-Attas is one of the figures whose ideas continue to be the current discussion and reference in highlighting Islam as a worldview in this contemporary time. Broadly speaking, the underlying thought of al-Attas is about the condition of the decline of Muslims in various living systems, especially in the educational sector and the development of science. In his works, al-Attas is generally focus on the idea of restoring the value of Islam as a worldview (re-actualization of Islamic teachings), carrying the independence of Islam from the dependency on the Western civilization (westernization) and from the idea of de-secularization. This is an effort to integrate Islamic science and restore the harmony between Islam and science. Therefore, al-Attas offers several renewal concepts such as: First, the Islamization of science, that is the process of deconstruction of Western science and then reconstruct into the Islamic knowledge system. Second, the concept of Islamic education that aims to create a perfect human being, a person who is aware of their individuality and relationship with God, society, and nature. Both are the embodiments of the re-actualization of the rise of Islamic civilization.Abstrak: Al-Attas adalah salah satu tokoh yang pemikirannya terus menjadi perbincangan dan acuan dalam menyoroti Islam sebagai pandangan dunia di era kontemporer ini. Secara garis besar, yang melandasi pemikiran al-Attas adalah situasi kemunduran umat Islam dalam berbagai sistem kehidupan, terutama dalam dunia pendidikan dan perkembangan ilmu pengetahuan. Maka dari itu, memang dalam karya-karyanya, al-Attas secara umum memfokuskan pemikirannya dalam mengembalikan nilai Islam sebagai pandangan dunia (reaktualisasi ajaran Islam), mengusung kemandirian Islam dari jeratan peradaban Barat (dewesternisasi) dan gagasan desekularisasi, suatu upaya mengintegrasikan ilmu-ilmu keislaman, mengembalikan keharmonisan antara agama (Islam) dengan sains. Untuk itu, al-Attas menawarkan beberapa konsep pembaharuan, seperti islamisasi ilmu yang merupakan proses dekonstruksi terhadap ilmu pengetahuan Barat untuk kemudian direkonstruksi ke dalam sistem pengetahuan Islam, dan konsep pendidikan Islam yang bertujuan menciptakan manusia paripurna, yaitu manusia yang sadar akan individualitasnya dan hubungannya yang tepat dengan Tuhan, masyarakat, dan alam. Keduanya adalah perwujudan dari reaktualisasi kebangkitan peradaban Islam.